Is Multicultural Islamic Education Still Relevant? A Critical Analysis of Moral Crisis, School Violence, and Student Apathy - Abdillah, Hilmy Alwy (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Contemporary schools increasingly face serious challenges such as moral degradation among students, bullying, school violence, and declining learning motivation. These phenomena raise critical questions regarding the relevance of multicultural Islamic education, which has long been promoted as a framework for character building and tolerance. This study aims to critically analyze whether multicultural Islamic education remains relevant in addressing moral crisis, school violence, and student apathy. The research employs a qualitative approach using a library research design by analyzing scholarly literature related to multicultural Islamic education, character education, and contemporary student behavior. The findings reveal that while multicultural Islamic education offers strong normative values rooted in tolerance, inclusivity, and ethical awareness, its implementation often remains symbolic and procedural. This limitation weakens its capacity to respond effectively to students’ moral and behavioral problems. The study further finds that school violence and learning apathy indicate deeper educational failures caused by the disconnection between educational values and students’ lived experiences. The study concludes that multicultural Islamic education remains relevant only when reconstructed as a transformative educational paradigm that integrates relational pedagogy, contextual moral engagement, and value-based school culture. Such reconstruction enables multicultural Islamic education to function as a meaningful response to contemporary moral and social challenges in schools.